Isu Pemanasan Global dalam Pergeseran Paradigma Keamanan pada Studi Hubungan Internasional - Sayyidati, Adibah (Universitas Muhammadiyah Yogyakarta, 2017)
For many years, International Relations (IRs) has focused its discussion on politico-military theme, where the states were the main actor in this study. This tradition is known as realism. As time went by, the golden age of realism paradigm comes to an end because it couldn’t cope with the complicated problem faced by international community. That is why IRs begins to broaden and deepen its object of discussion to non-military topics, such as economics, politics, social, and environment. In a brief, IRs discourse moves from state security to human security. As what has been explained, economics is one of many sectors that get attention the most because this theme related to human activity on fulfilling their daily basic needs. But, this activity causes undesired effect to the environment, such as global warming, that should be handled as soon as possible. It encourages international community to begin paying attention to this issue at last decade. Global warming as the one of the biggest issue in environmental security is the trigger of it. This topic also made environmental issue to be IRs focus of study as well as another aspect, such as military, economics, and politics.Artikel ini memaparkan perubahan jangkauan pembahasan studi Hubungan Internasional (HI) dari tema-tema politik dan militer di mana negara menjadi aktor utama dalam disiplin ilmu ini yang kemudian berkembang menjadi tema-tema seperti ekonomi, sosial, dan lingkungan sehingga tidak lagi hanya fokus pada topik-topik politik dan militer. Dengan kata lain, disiplin ilmu HI telah menggeser fokus obyek kajiannya dari keamanan negara menjadi keamanan manusia yang meliputi tema-tema non-militer. Ekonomi menjadi salah satu bidang yang mendapat perhatian lebih karena aspek ini terkait dengan aktifitas manusia untuk memenuhi kebutuhan hidupnya. Namun aktifitas ekonomi ini juga membawa efek samping, seperti pemanasan global, yang harus ditangani seefektif mungkin. Inilah yang melatarbelakangi besarnya perhatian komunitas internasional pada fenomena tersebut dalam beberapa dekade terakhir. Pemanasan global ini juga mengantarkan tema lingkungan untuk menyejajarkan dirinya dengan aspek-aspek lain seperti ekonomi dan politik sebagai fokus kajian HI.